Enhancing Adolescent Health through Anemia Prevention Education and Hemoglobin Testing to Reduce the Risk of Stunting - Dessy Lutfiasari; Alfika Awatiszahro; Betanuari Sabda Nirwana; Khofidhotur Rofiah (Journal of Community Engagement in Health, 2025)
Stunting can begin as early as adolescence, particularly through anemia in young girls. Anemia occurs due to a lack of hemoglobin, especially during menstruation. If not properly addressed, it can lead to stunting. In Indonesia, the anemia rate among adolescents remains high, reaching 32% in 2018 and declining to 15.5% in 2023. According to the WHO, this figure is still considered high, as it remains above 10%. The purpose of this community service activity is to increase adolescent knowledge and skills regarding anemia prevention. The community outreach activities included pre-test and post-tests, giving health education, and hemoglobin level checks. Results showed that knowledge before the health education was less of knowledge (84.3%), but after the health education increased to 86.8% in good knowledge. Furthermore, hemoglobin level checks revealed that 37% of students had anemia, with half of these having moderate anemia. This community service activity can be a way to prevent anemia through health education and hemoglobin level checks, thereby increasing knowledge about anemia prevention and stunting prevention.